The Importance of Agrotechnical Measures in the Fight Against Garden Pests - Yuldasheva Shokhista Kobiljonovna; Saydaliyeva Roxatoy Zaylobidinovna; Askarova Gulmira Numonjon kizi; Obidova Gulmiraxon Farxodjon kizi (Peerian Journals Publishing, 2022)
New advances in science and technology will be used, along with basic data, including plant protection, forecasting and quarantine services. In solving these tasks, the analysis of orchards, protection and expansion of existing orchards from destruction are important measures. Using agro-technical methods can prevent the reproduction of pests, and sometimes completely eradicate them. Successful application of agro-technical methods can create unfavorable conditions for pests, create favorable conditions for the good growth of free plants and the proliferation of entamophages. The development and damage of pests often depends on the natural environment, the amount of food, the suitability of temperature and humidity for the pest, and other environmental conditions.
Keywords: forecasting; quarantine; agrotechnical method; entamophagous